Factors Affecting the Not Implementation of Medical Record Tracer - Sulisna, Aida; Meliala, Sri Agustina; Fauzi, Muhammad (Jurnal Perilaku Kesehatan Terpadu, 2023)
Tracer is an important tool in controlling the use of medical record files. Usually used to replace medical records that are out of storage. These exit instructions remain in storage until the borrowed medical records are returned and stored again. This exit sign is equipped with a pocket for storage of request slips. The purpose of this study was to determine the factors that influence the non-application of a medical record tracer at the Pratama Klambir clinic in 2021. This research method used a descriptive qualitative method which was carried out from November to completion. The informants of this research were 6 informants, namely 1 key informant, 4 main informants and 1 triangular informant obtained by purposive sampling technique.The study obtained the man factor (human resources), namely the education of officers who did not graduate from medical records and had never attended training, machines (machines) that had not been applied to the use of tracers and lacked storage racks, materials (raw materials), namely the folders used were still made of plastic and had not used color codes, methods (methods/procedures), namely SPO had not been carried out properly, and money, namely there was a shortage of money. The conclusion in this study is that there are many factors (human resources), machines (machines), materials (raw materials), method (methods/procedures) and money (money) which causes the medical record tracer not to be applied at the Pratama Klambir clinic.